Ultrasound Guided Hydrostatic Versus Open Reduction in Intussusception: Ultrasound Guided Hydrostatic Reduction - Hameed, Soban; Haider, Naveed; Rehman, Wajeeh Ur; Hashim, Imran; Ahmed, Armaghan; Shahbaz, Ferheen; Saleem, Muhammad (Pakistan Journal of Health Sciences, 2022)
The surgical and nonsurgical technique has been utilized to manage intussusception. Surgical management of intussusceptions involves open laparotomy along with manual reduction. The non-surgical technique, Ultrasound-guided hydrostatic reduction (USGHR) is a renowned alternative technique for intussusception reduction. Objective: To compare the ultrasound-guided hydrostatic reduction versus open reduction for the management of intussusception in terms of successful reduction, recurrence, and hospital stay. Methods: It was a randomized controlled trial in which 158 cases were admitted through the Emergency Department of Pediatric Surgery of The Children’s Hospital Lahore, from August 2018 to August 2019. These patients were divided into 2 groups (79 in each group), Group A (ultrasound-guided hydrostatic reduction) and group B (open reduction). Data were collected through a questionnaire, which was entered into the computer using SPSS version 24.0. Results: Among 79 patients treated in-group A, 54.4% were up to 12 months old, and 67.1% males, in this group the hospital stay for 74.7% was 1-2 days and 74.7% had a successful reduction. In group B; patients treated in group B, 77.2% were up to 12 months old, and 72.2% were males. The hospital stay for 59.5% of patients was 5-7 days, and 83.5% had a successful reduction of intussusceptions. The recurrence was only in group B (3.8%) after the reduction of intussusceptions. Conclusion: The study concluded that ultrasound-guided hydrostatic is effective in terms of successful reduction, recurrence and hospital stay and should be preferred among children due to its safety and effectiveness.